Breastfeeding promotion: evidence and problems - Roberto Bellù; Manuela Condò (PAGEPress Publications, 2017)
Although breastfeeding is associated with many health benefits in children and mothers, and World Health Organization (WHO) recommends exclusive breastfeeding until 6 months of age and continued breastfeeding until 2 years of age, overall breastfeeding rates remain low. Italian rates of exclusive breastfeeding do not differ from international data. The aim of this review is to evaluate evidence of breastfeeding promotion interventions and the remaining problems to achieve them. We found that breastfeeding support is a complex system of interventions, including individual, structural and environmental factors. Many systematic reviews report evidence that breastfeeding support offered to women increases duration and exclusivity of breastfeeding, both in full term healthy newborns and in preterm infants. Political and economic efforts should be made to ensure breastfeeding support to all women in the different settings, assuming it as a collective target.